Binding of the cytoplasmic domain of CD28 to the plasma membrane inhibits Lck recruitment and signaling - Dobbins, Jessica (Sci Signal, 2016)
The T cell costimulatory receptor CD28 is required for the full activation of naïve T cells and for the development and maintenance of Foxp3(+) regulatory T (T(reg)) cells. We showed that the cytoplasmic domain of CD28 was bound to the plasma membrane in resting cells and that ligand binding to CD28 resulted in its release. Membrane binding by the CD28 cytoplasmic domain required two clusters of basic amino acid residues, which interacted with the negatively charged inner leaflet of the plasma membrane. These same clusters of basic residues also served as interaction sites for Lck, a Src family kinase critical for CD28 function. This signaling complex was further stabilized by the Lck-mediated phosphorylation of CD28 Tyr(207) and the subsequent binding of the Src homology 2 (SH2) domain of Lck to this phosphorylated tyrosine. Mutation of the basic clusters in the CD28 cytoplasmic domain reduced the recruitment to the CD28-Lck complex of protein kinase Cθ (PKCθ), which serves as a key effector kinase in the CD28 signaling pathway. Consequently, mutation of either a basic cluster or Tyr(207) impaired CD28 function in mice as shown by the reduced thymic differentiation of FoxP3(+) T(reg) cells. On the basis of these results, we propose a previously un-described model for the initiation of CD28 signaling.